Valorizzazione e fruizione dei punti di interesse culturale e turistico: il caso del Municipio VII di Roma - Guido, Roy Andrea (Archeomatica, 2019)
A case history in the VII Municipal District of Rome, between cultural and touristic valorisation and enjoyment, based on the participation of citizens, schools and other civic entities called to identify and catalog points of cultural interest which are recognizable as such and can be communicated in cultural terms (archeological areas and monuments, places of urban fabric). These are then combined to constitute cultural and tourist itineraries passing through the suburbs of Rome, and are enhanced by stories by citizens for citizens, in their capacity as prosumers (producers, propagators and users of the content and of the stories relating to their local heritage).